The invisible war : what every believer needs to know about Satan, demons, and spiritual warfare - Ingram, Chip, 1954- (Grand Rapids, MI : Baker Books, 2006)
Examines what every believer needs to know about Satan, demons, and spiritual warfare. This provocative book helps Christians understand what the Bible says about these threats and shows them how they can safeguard themselves and their families through prayer.
Why you struggle -- Your life : behind the scenes -- You have a personal enemy -- Our strategic position -- Your personal "code red" -- Sifting through false intelligence -- In sync with God -- Bombarded by doubts -- When you're attacked -- Cultivate invincible faith -- The battle for your mind -- Wield your weapons -- The missing ingredient of your life -- When the enemy gets in -- How to find freedom -- A tale of two warriors.
Includes bibliographical references (page 189).
Keywords: Spiritual warfare; Demonology; Devil -- Christianity; Good and evil -- Religious aspects -- Christianity; Demonology; Devil -- Christianity; Good and evil -- Religious aspects -- Christianity; Spiritual warfare